Quantifying the sectoral contribution of pollution transport from South Asia during summer and winter monsoon seasons in support of HTAP-2 experiment. (November 2016) - Surendran, Divya E.; Ghude, Sachin D.; Beig, G.; Jena, Chinmay; Chate, D.M.
Abstract: This study examines the contribution of 20% reduction in anthropogenic emissions from the energy, industry and transport sectors in South Asia to global distribution of ozone (O3 ) during summer and winter monsoon seasons. We used Model for Ozone and Related chemical Tracers (MOZART-4) and Hemispheric Transport of Air Pollution version-2 (HTAP-v2) emission inventory to simulate global O3 for five different sensitivity simulations. Contribution from different emission sectors is identified on the basis of the differences between model calculations with unperturbed emissions (Base-case) and the emissions reduced by 20% by different sectors over South Asia. During the summer season, 20% reduction in emissions from transportation sector contributes maximum decrease in O3 of the order of 0.8 ppb in the center of Asian Summer Monsoons (ASM) anticyclone at 200 hPa. Response to Extra Regional Emission Reduction (RERER) is found to vary between 0.4 and 0.7 inside the ASM, indicating that 40–70% of O3 trapped inside the anticyclone is influenced by the emission from non-Asian emissions, and the remaining O3 is influenced by South-Asian emissions. During winter, 20% reduction in emissions from transport sector contributes decrease in O3 at surface up to 0.5 ppb over South Asia and outflow region (the Arabian Sea and the Bay of Bengal). RERER values vary between 0 and 0.2 over South Asia indicating the predominant impact of local emissions reduction on surface O3 concentration than reduction in foreign emissions. We have also examined the health benefits of reduction in regional, global and sectoral emissions in terms of decrease in excess number of COPD (Chronic Obstructive Pulmonary Disease) cases due to O3 exposure. We find that more health benefits can be achieved if global emissions are decreased by 20%. Highlights: Contribution of emissions from the energy, industry and transport sector from South Asia to global distribution of O3 . Response to Extra Regional Emission Reduction on surface O3 over South Asia. Health benefits from reduction in sectoral, regional and global emissions.